2019
DOI: 10.3390/app9173615
|View full text |Cite
|
Sign up to set email alerts
|

Flow Analysis Based on Cathodic Current Using Different Designs of Channel Distribution In PEM Fuel Cells

Abstract: In this work, a physical and numerical simulation of cathodic current for different designs of the channel distribution in PEM fuel cells was carried out. The first design consisted serpentine-type channels with abrupt changes in flow direction. On the other hand, Designs 2 and 3 were made of serpentine channels with a more gradual change in flow direction. The fourth design was a crisscross-type channel, which was based on continually redirecting the flow, while Design 5 was made with straight parallel channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Saripella et al researched the influence of bio-inspired flow channels on the performance of PEMFC by simulation and experiment [20]. Zamora-Antuñano et al made a CFD model of a PEMFC and analyzed the influence of channel distribution on the cathode current [21]. Each flow field design has certain disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Saripella et al researched the influence of bio-inspired flow channels on the performance of PEMFC by simulation and experiment [20]. Zamora-Antuñano et al made a CFD model of a PEMFC and analyzed the influence of channel distribution on the cathode current [21]. Each flow field design has certain disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the 10‐channel serpentine flow field generated up to seven times lower pressure drop values compared to conventional serpentine designs. Zamora‐Antuñano et al tried to solve flooding issues in the 90° bends of serpentine channels by simulating them with curvilinear bends and crisscross patterns 15 . A significant increase in current density was observed due to the even distribution of oxygen concentration at the cathode, but pressure drop levels were still high as the reactants had to force through the small connector in between each serpentine layer.…”
Section: Introductionmentioning
confidence: 99%
“…Zamora-Antuñano et al tried to solve flooding issues in the 90 bends of serpentine channels by simulating them with curvilinear bends and crisscross patterns. 15 A significant increase in current density was observed due to the even distribution of oxygen concentration at the cathode, but pressure drop levels were still high as the reactants had to force through the small connector in between each serpentine layer. Since conventional designs are becoming saturated, novel flow field designs are actively explored.…”
Section: Introductionmentioning
confidence: 99%